Unitized curtain wall systems joint performance with re-entrant corners under seismic racking testing. (August 2021) - Memari, Ali M.; Simmons, Nick; Solnosky, Ryan L.
Abstract: Understanding damage mechanisms and associated facility challenges for curtain wall systems with different boundary conditions is critical in their performance evaluation and selection during the design stage of a building's lifecycle, in particular if vulnerable to earthquake effects. While many different styles and configurations exist, limited research has been conducted on unitized four-sided structural sealant glazing (4SSG) with re-entrant corners under dynamic racking testing conditions. As such, this paper details a study on full-scale unitized 4SSG curtain wall system mockups featuring a re-entrant corner and subjected to cyclic racking displacements. Racking tests were carried out in accordance with the American Architectural Manufacturers Association (AAMA) 501.6 protocol. Glass fallout, sealant adhesive or cohesive failure, and glass cracking failure modes were identified as limit states and corresponding drift levels were determined. Results of these tests on full-scale specimens are presented here and some of the challenges in data collection and accuracy when using a racking facility are discussed.